(untitled) (Heritage, 2021)
This paper deals with geography lexics and terminology found in a Mirko Banjević poem Sutjeska. This poem has been published several times. It was published just after the First World War for the first time in 1946 by “Pobjeda” from Podgorica, and then it was published by publishing house “Rad” from Belgrade in 1953, publishing house “Kosmos” from Belgrade in 1958 and finally by Yugoslav academy of sciences and arts from Zagreb in 1961. Materials used in this paper came from the Kosmos edition from 1961.